Innovative Strategies for Lean Manufacturing Laboratory: A Literature Review on Automation and Planning - Qulub, Irkham Syifaul; Herlambang, Hendi; Amrina, Uly; Ikatrinasari, Zulfa Fitri (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
This research investigates the evolution of laboratory practices, lean manufacturing, and automation. It involved analyzing 150 scholarly articles retrieved from Google Scholar using keywords "Laboratory, Lean Manufacturing, and Automation," selecting and studying 49 relevant articles. Key findings highlight trends in smart laboratory development, lean manufacturing implementation, and automation integration in industry. Limitations include insufficient focus on highly automated lean laboratories and the need for comprehensive planning across short, medium, and long terms. Future research should explore innovative strategies to improve laboratory efficiency and industrial responsiveness. This study offers insights into current academic trends and suggests paths for sustainable technology development in laboratories and lean manufacturing